Analisis Pengaruh Suku Bunga Pinjaman terhadap NPL dan Laba (Studi pada PD, BPR Bank Daerah Tulungagung) - Wahyu Andika Rani (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This Research aims to know the influence of interest rate toward NPL (Non Performing Loans) and Profit. This research used discriptive kuantitative method. The subject of this research is PD BPR Bank Daerah Tulungagung. For the data collection the researcher used publication report of PD BPR Bank Daerah Tulungagung that was on the OJK (Otoritas Jasa Keuangan) website on period 2013-2018. Then the data are processing use SPSS (Statistical Package for Social Science) for windows version 21. Based on the result of research by linear regression simple analysis there are significant impact between interest rate to NPL (Non Performing Loans). Meanwhile the result of interest rate to profit showed the significant positive. In otherwise the result of NPL (Non Performing Loans) to Profit showed the significant on level 20%. In other word, the reasecher conclude that interest rate influential between NPL (Non Performing Loans), interest rate influential between Profit PD BPR Bank Daerah Tulungagung, and NPL (Non Performing Loans) influential between profit